2018
DOI: 10.1021/acs.est.8b02133
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Microbe Interactions Drive Denitrification Rates, Dissolved Nitrogen Removal, and the Abundance of Denitrification Genes in Stormwater Control Measures

Abstract: The microbial community and function along with nitrate/nitrite (NOx) removal rates, and nitrogen (N) partitioning into "uptake", "denitrification", and "remaining" via isotope tracers, were studied in soil bioretention mesocolumns (8 unique plant species). Total denitrification gene reads per million (rpm) were positively correlated with % denitrified ( r = 0.69) but negatively correlated with total NOx removal following simulated rain events ( r = -0.79). This is likely due to plant-microbe interactions. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…S4), indicating that there was not a notable selective loss of members of the community at the agricultural field site. Complex N-competition relationships with crop plants might account for lesser nar read abundance at the agricultural field site (Morse, 2018), but it is unclear why this would not likewise impact nap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S4), indicating that there was not a notable selective loss of members of the community at the agricultural field site. Complex N-competition relationships with crop plants might account for lesser nar read abundance at the agricultural field site (Morse, 2018), but it is unclear why this would not likewise impact nap.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence comparisons to identify reads derived from N-oxide genes were done using DIAMOND (Buchfink et al, 2015). Taxonomic assignment of metagenomic reads was performed using a clustering and alignment-based approach, which is described in the study by Morse et al, 2018. These data sets were manually curated to confirm protein assignments and are available at http://hdl.…”
Section: Metagenomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis through Kruskal-Wallis test indicated that there was no significant statistical difference between the inlet and outlet median TN concentrations for all groups as p > 0.05 (see Table 3). Therefore, TN concentration was independent from depth for Cyperus and Pedilanthus in the box biofilter, and this was likely because of little or no denitrification in the biofiltration system [46,47]. Further analyses were conducted to either prove or reject the hypothesis of correlation between TN removal and depth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work researching bioretention systems have used local climate data to determine dosing volumes. Chandrasena et al (2017) report using a storm size of 5.75 mm per event while Glaister et al (2017) and Morse et al (2018) used a local yearly average of 540 mm. Each storm event was applied based on 20:1 sizing ratio for each column (TSM 2015).…”
Section: Stormwater Applicationmentioning
confidence: 99%